A Workshop and Toolkit to Support Late-Career Transitions for Faculty - Virginia Niebuhr; Pamela Wood; Judith Livingston; Fred Henretig; Andrew Sirotnak; Janet Williams; David Jaffe (MedEdPORTAL)
Introduction Twenty percent of medical school faculty are 60 years or older. These senior-career academic faculty often find a paucity of support for decision-making about late-career transitions. Methods To help fill this professional development gap, we developed and tested an interactive workshop to facilitate deliberation and discussion among mid- and late-career faculty in various stages of career transition planning. The workshop included individual and small-group activities and a takeaway packet/toolkit for career transition planning. We conducted mixed methods analyses of postworkshop survey data to evaluate the workshop content, methods, and toolkit. Results The workshop was implemented six times, at four national conferences, one state-level conference, and one single institution, for a total of 207 participants. Evaluations were completed by 60% of participants. Thirty-one percent were thinking generally about transition, 40% were making specific plans for transition within 1–5 years, 15% were currently in transition, and 10% had fully transitioned. Perception of workshop objectives met received a median ranking of 4 (rated on a 5-point Likert scale). Participants reported positive outcomes, including taking time to think/reflect, finding starting points for transition planning, and sharing conversations. Discussion This highly rated, interactive workshop provides support and practical tools for faculty considering late-career transitions. In addition to providing resources for individual faculty, this workshop has value for an institution to support their senior-level faculty. We encourage the incorporation of this workshop into institutional faculty development programming to ensure a career lifespan approach to faculty development.